دراسة وحساب عمق المجال النشط ضوئياً لأغلفة عاكسة للضوء أساسها مساحيق أكسيد الزنك - سليمان, حسن (Latakia University Journal -Basic Sciences Series, 2017)
نعرض في هذا البحث نتائج دراسة وحساب عمق المجال النشط ضوئياً لغلاف عاكس لضوء بطريقة الانتثار تبعاً لتشتتية أو انتثارية حبيبات الصبغة المستعملة في الغلاف ولطول موجة الإشعاع الكهرطيسي الوارد عليه حيث تغيرت أبعاد حبيبات مسحوق أكسيد الزنك ضمن المجال من حتى . يدخل في تركيب الغلاف العاكس للضوء مسحوق أكسيد الزنك ZnO وطبقة عضوية تكون بمثابة غشاء رابط. كما تم حساب أعماق المجال النشط ضوئياً للغلاف العاكس للضوء بطريقة الانتثار عند تغير معامل امتصاص الصبغة الداخلة في تركيب الغلاف (ZnO / رابط) ضمن المجال من إلى أكثر من . إن النتائج التي حصلنا عليها في هذا البحث تسمح لنا بتحسين سماكة الأغلفة العاكسة للضوء بطريقة الانتثار لدى تحضير أنواع محددة منها.In this research we present results of the studying and calculating the optically active range depth for diffuse light reflected coating at change of the dispersiveness of pigment grains used in coating and wavelength of incident electromagnetic radiation. This coating consists of zinc oxide powder and organic material that acts as a binding film. The size of zinc oxide powder grains were changed between and . In addition, the depths of optically active range of diffuse light reflected coating were calculated when the absorption coefficient of the pigment used in the ZnO/binder coating changed between and . The obtained results allow us optimization of the diffuse light reflecting coatings thickness at preparation determined kinds of them.